Variasi Warna Pipet pada Stik Perangkap Lalat terhadap Jumlah Lalat yang Tertangkap - Iqbal Ardiansyah; Bambang Wispriyono; Indah Werdiningsih; Rizki Amalia (Faculty of Public Health, Hasanuddin University, Makassar, 2019)
Flies are vectors of disease. In the section of chicken slaughter, Pasar Gedebage has a high fly density of21 tails / block grill hence it is necessary to control one of them fly sticky trap. The purpose of the study was todetermine the effect of straw color variations on the number of flies caught in fly trap sticks with the type of quasi-experimental research and post-test only design. This research was conducted at HS Pasar Gedebage Bandungchicken slaughterhouse on 25 to 30 December 2017 with research subjects all flies were in the study location. Thematerial in this study is white, yellow, red and blue straw. 3/4 straw surface smeared with durian flavored fly glue.The method in this study is quantitative research, analyzed descriptively and statistically tested. The statisticaltest begins with the normality test of Shaphiro Wilk, then tests on one way ANOVA and Post hoct LSD test. Theresults of the study were that the number of flies trapped in the white straw was 32,6 on average, the average yellowstraw was 24, the red straw was on average 18 and the blue straw was 16 on average. Statistical test resultsp-value 0.0005 shows the difference between each color straw with the number of flies caught, the white straw isthe color of the straw that traps the most flies. The conclusion research white color of straw is the best color strawfor making fly sticky trap.